Intangible Assets: Are These Resources Sufficiently Visible and Properly Controlled? - Adriana-Sofia Dumitrescu (Journal of Accounting and Management Information Systems (JAMIS), 2012)
The current context of market based economy has highlighted the great importance of intangible assets because innovation is considered to be the major factor for economic growth. Whether they are labeled as intangible assets, invisible assets, knowledge capital, core competences, etc., these assets rely on information and knowledge and they add and create value for the company. The article aims to reveal how Romanian companies disclose information about such elements. Referring to the employed research methods, the article is based on a comparative analysis of the information on intangible assets presented in the Annual Reports by a sample of Romanian companies listed at Bucharest Stock Exchange. In order to assess if Romanian companies disclose sufficient information on intangible assets, a standard of disclosures format was firstly conceived and secondly the information disclosed by the sample companies was compared to the standard. Although the capacity for innovation of a company, the intellectual capacity of employees, the internal skills developed within a company (know-how, organization, etc.), the owned patents and technologies, trademarks, the awareness of each brand, the relationship with customers are all identifiable elements that must be taken into account if we want to determine the real value of a company, our study reveals that many Romanian companies listed at Bucharest Stock Exchange do not grant enough importance to disclosing detailed information on the intangible assets in their Annual Reports. This situation may arise because of the lack of awareness or because of the fact that their measurement is most of the time extremely difficult. In this context, based on the conceived standard of disclosures format, our article tries to build a model that will help companies to identify, assess and control their intangible assets. Our proposed model is a suggestion for the presentation of the company's intangible assets and it can be used not only for internal purposes (intangibles' management) but also for external purposes (disclosure of non-monetary information that informs investors on the company's resources and potential). The presented model can be considered a guideline which can be easily adapted by companies accordingly to their informational needs.
Keywords: M41; O30; 650; Intangible assets; intellectual capital; innovation; intangibles management; assessing intangible assets; model